Associação de morfina e clonidina na anestesia peridural caudalcom Bupivacaína: estudo prospectivo randomizado duplo cego - Magda Lourenco Fernandes (2010)
The adequate control of postoperative pain is very important for the children care. It is very difficult to access and classify the severity of pain in this group of patients. Among the analgesia techniques available, caudal epidural anesthesia is a good choice providing a favorable risk-benefit relation. Several local anesthetics and adjuvants drugs have been studied to improve analgesia quality and reduce side effects. The aim of this study was to investigate the efficacy of the association of morphine and clonidine to bupivacaine in caudal epidural block. We alsoevaluated the behavior of the biespectral index (BIS) in children undergoing general anesthesia with isoflurane combined with caudal anesthesia. On this prospective, randomized and double-blind study, eighty pediatric patients of both genders, ranging from one to ten years- old, were submitted to genital or urinary surgery by inhalation anesthesia combined with caudal epidural block. The patients were separated into four groups that received 1 ml/Kg of four different solutions in the caudal epidural space: 0.166% bupivacaine with epinephrine (B group); 0.166% bupivacaine with epinephrine plus morphine 20 ìg/Kg (BM group);0.166% bupivacaine with epinephrine plus clonidine 1 ìg/Kg (BC group) and, 0.166% bupivacaine with epinephrine plus morphine 20 ìg/Kg and clonidine 1 ìg/Kg (BMC group). The following parameters were evaluated during the surgery: heart rate (HR), mean blood pressure (MBP), BIS and isoflurane expired fraction. During the postoperative period the intensity of pain, the use of analgesic drugs and the incidence of side effects were evaluated. The behavioral FLACC scale (face/legs/activity/cry and consol ability) and the face scale by Wong-Backer were used to evaluate the pain. During the surgery there was no statistically significant difference between the groups regarding HR, MBP, BIS and expired fraction ofisoflurane. Only three patients received intravenous fentanyl during anesthesia that was not statistically different. The pain scores and duration of analgesia were similar between groups. Patients who used caudal morphine (BM and BMC) more rarely needed to use analgesics postoperatively (p = 0.024), but a higher incidence of nausea and vomiting (p = 0.025). The BIS correlated better with the expiredconcentration of isoflurane than with hemodynamic data and presented great individual variability, with higher values in younger children. In conclusion, caudal epidural block with morphine, clonidine or both did not provide any additional effect on analgesia obtained with 0.166% bupivacaine after pediatric genitourinary surgery. In children, the use of BIS seems to be limited due to the variability and imprecise limits.